Stroke in the young: relationship with iron deficiency anemia and thrombocytosis - Basak, R; Chowdhury, AM; Fatmi, LE; Saha, NC; Mollah, AH; Yasmin, S (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):74-7. The abstract of this article is available on the PubMed website